AS PRESCRIÇÕES PARA O ENSINO DE INGLÊS: UMA RELAÇÃO ENTRE O LIVRO DIDÁTICO E O PLANEJAMENTO DO PROFESSOR - LOPES, MONICA (2017)
The choice of proper materials consistent with the school reality demands understanding about the didactic material analysis. This research aimed to analyze the relationships between the configurations of the textbook, the educational prescriptions and the working planning. We sought to understand the prescriptions for reading, writing and speaking proposals in the Way to go textbook and in teaching plans built by teachers in relation to Educational Guidelines. The book is one of those approved in the National Textbook Plan for the year of 2015 for High School and it was chosen by teachers from thirteen public High schools from Guarapuava-PR for 2015 to 2017. The documentary research comes from of a corpus composed by the textbook and by two Annual Teaching Plans (ATPs) of 1st year of High School. The research is based on studies on DCELEM (PARANÁ, 2008), planning (ROJO, 2001), prescribed and planned work Machado (MACHADO, 2005), didactic transcription and prescriptions (SCHNEUWLY, 2009; MACHADO, 2002), the proposal of textual genres under the bias of Socio - discursive interactionism (BRONCKART, 1999, CRISTOVÃO, 2002) and language capacities (DOLZ, PASQUIER and BRONCKART, 1993), (CRISTOVÃO et al, 2010), CRISTOVÃO; STUTZ, 2011). The analyzed unit of the book comes from the genres: photos of sustainable and unsustainable practices, procel stamp, mind map, plates and radio program. The activities mobilized the action capacities, discursive capacities, linguistic-discursive capacities and signification capacities. Although it addresses several genres, the major focus is not on the genres but on the theme. The focus genre of the unit is the mind map, although it involves the study strategies that contribute to the student to improve the ways of synthesizing contents, it does not lead to the practice of the social discourse prescribed in DCELEM and in the ATPs. Even the language capacities being exploited are not directly associated with social practice. Therefore, the work adopts the dialogic perspective of language, and the conception of genrer adopted in socio-historical-cultural perspective (VYGOSTKY, 1984). The ATPs refer to the textbook Way to go and are planned from the DCELEM (PARANÁ, 2008). The goals are not for each genrer, but specific for the work with reading, writing and speaking, according to DCELEM. Thus, the ATPs analyzed are constructed by the structuring content as social practice and the contents of reading, speaking and writing through the textual genres. The recurrent genre in the ATPs is comic book. The concept of language underlying the plans is the discursive one based on DCELEM and in the textbook. Thus, ATPs have a strong relationship with DCELEM (2008), as it is one of the Educational Guidelines of the teacher's practice in teaching institutions and with the textbook. ISD, the sociodiscursive interactionism conception of language we choose will resonate who we are and the ideal of society we seek, through the conditions we offer so that our students recreate the world around them. Therefore we concluded that the teacher's work is guided by the prescriptions of the Educational Guidelines and also by the Political Pedagogical Project as well as the Curricular Pedagogical Proposal, on which the teachers need knowledge, until configuration in the ATP.